Da'wah on Air: Case Study on Batam Radio Islamic Broadcasting - Pamungkas, Poetut Ariyo Tejo (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2024)
This study aims to find out about 1) Management of Hang FM Radio in Batam as a propaganda radio 2) Constraints and drivers so that Hang FM Radio broadcasts can exist. Hang FM radio is an Islamic da'wah radio in Batam City. The city of Batam which consists of 400 islands is very suitable for the nature of radio. The propaganda material broadcast by Hang FM Radio was easily accepted by the audience, even outside the island of Batam. The purpose of the study was to determine the management of Hang FM radio as well as the factors that encourage and inhibit the management of Hang FM radio. The methodology in this study uses a qualitative descriptive approach. Data were obtained through interviews, and documentation studies. The results showed that the management of Hang FM Radio did planning, Organizing, Motivating and Controlling with the central control of the Hang FM founder. This central figure is the driving factor for the existence of Hang Radio broadcasts to date. The conclusion of this research is that the implementation of Hang FM Radio's media management function rests on the character of the Hang FM Radio Founder. The driving factor for Hang FM radio broadcasts is religious motivation and the determination of the leader. The inhibiting factors faced are differences in the views of the manhaj and the lack of public understanding of the sunnah da'wah and the salaf manhaj.